Estudo comparativo entre enxertos de hidroxiapatita e gesso paris na reparação óssea em calvária de ratos - Branco, Antonio Carlos Lopes (2011)
The use of bone graft materials that promote the regeneration, it is a fact quite common in rehabilitation procedures. Various materials are used for this purpose, but among them, the plaster paris, which was one of the forerunners of this line fell into disuse at the expense of more elaborate materials. The objective of this study was a comparative analysis between the plaster paris and resorbable hydroxyapatite, to establish a degree of reliability of use for this material today as an option for low cost and easy handling. For this, an analysis was performed on 36 female Wistar rats with the use of these materials, for subsequent histological analysis of wound repair. This study demonstrated that in this situation, there was no difference in the potential of bone repair by comparing the two materials and the control group using only a blood clot, as well as the excellent biocompatibility of the same with the negative potential to produce unwanted reactions.